Evaluation of an education intervention for Australian health practitioners to support people with dementia with driving decisions: A pretest-posttest survey. (28th June 2022) - Veerhuis, Nadine; Traynor, Victoria
Abstract: Objective: Drivers with dementia will at some stage need to stop driving. The timing of driving retirement is informed by the advice of health practitioners, however many find this task complex and challenging as they feel unprepared or lack confidence, having limited training and education on dementia and driving. Few opportunities exist for Australian health practitioners to advance learning about dementia and driving. This study evaluated the impact of a Dementia and Driving Education Module on practitioner self-perceived knowledge, confidence, and competence in supporting people living with dementia with decisions about driving. Methods: A single group, pretest-posttest survey was conducted for this study. Health practitioners were recruited over 19 months via email and invited to attend a face-to-face dementia and driving workshop. The workshop comprised of a two-hour Dementia and Driving Education Module including seven learning activities incorporating six vignettes, five self-reflections, one case study and a paper copy of a dementia and driving decision aid. Participants completed a survey prior to, immediately after and six weeks post completion of the education module. Results: A total of 240 health practitioners, from over six disciplines, took part in one of eleven workshops delivered via face-to-face and online across five states of Australia. Significant increases occurred in all outcome measures of perceived knowledge, confidence and competence between baseline and immediately post-education module survey responses and between baseline and six weeks post-survey responses. Conclusions: The Dementia and Driving Education Module and accompanying decision aid demonstrate an efficacious solution for a diverse range of health practitioners to enhance their knowledge, confidence, and competence in supporting people living with dementia with driving retirement decisions.